TINJAUAN HUKUM POSITIF DAN HUKUM ISLAM TERHADAP EFEKTIVITAS PENDAYAGUNAAN ZAKAT PRODUKTIF PADA PENINGKATAN USAHA MIKRO MUSTAHIK PENGUSAHA - Fitri Robbany; Irvan Iswandi (Melati Institute, 2022)
Zakat with good management is the potential fund source which can be utilized to advance public wealth for the community included MSME as one of business that can help economic development in a country. BAZNAS has a program namely productive zakat as explained in The Constitution Number 23 Year 2011. Productive zakat one of which is used to help mustahik’s MSME empowerment until there is development in their enterprise. This productive zakat aims if beforehand the mustahik could become muzakki. The purpose of this research is to find out the effectiveness of productive zakat empowerment in the improvement of micro enterprise and to find out how is the Islamic law perspective and positive law point of view. The research type used was field research. This research was descriptive qualitative which can analyze and describes the research results by investigating and studying productive zakat empowerment in the improvement of micro enterprise with data collection techniques used were observation, interview, and documentation. The results of this research show that productive zakat empowerment given to the mustahik is effective because they can run their business sustainable and continuos to increase in accordance with the purpose of positive law in the constitution number 23 year 2011 about productive zakat which becomes the countermeasure for the poor and to increase the economy of MSME doers. Until the implementation of productive zakat can decrease poverty in that area and poverty in Indonesia, however it is not in line with Islamic Law yet that those who have right to obtain zakat are 8 sanaf, while some mustahiks are not people who really need zakat and they are wealthy enough.